The Long Quest for an International Order with Chinese Characteristics: A Cultural Perspective on Modern China's Foreign Policies1. (4th August 2013) - Connolly, Chris; Gottwald, Jörn‐Carsten
Abstract : The role of the People's Republic of China in international relations (IR) is academically contested and politically crucial. While the dominance of (neo‐)realist perspectives of China's rise as a threat to the current order is receding, new approaches in the study of the foreign policies of the People's Republic of China and their impact on global issues are needed. This paper follows Lebow's cultural theory of IR by adapting the categories of "appetite" – Lebow's code for material interests – and "spirit" – non‐materialistic objectives, such as prestige or international standing – to the study of Chinese foreign policy‐making since the Xinhai revolution. The paper argues that China seeks to transform the system not merely as a means of attaining prestige or other liberalist or realist concerns. One of the key defining images of Chinese elites over time has been – and continues to be – one of China as a leading civilization setting global norms and standards. Applying Lebow's theory to foreign‐policy making therefore allows the integration of a normative dimension without immediately entering the dogmatic clashes among IR theorists. By proposing a long‐term perspective on China's engagement with the international system over the past 100 years, we assert that the desire for prestige and honor within the international system is one key determinant in China's behavior. Clearly, it cannot explain all of China's foreign policy choices. It highlights, however, how China's self‐esteem has meant that it has constantly sought to remake the rules to take account of China's own self‐image.